Bone marrow findings of idiopathic Multicentric Castleman disease: A histopathologic analysis and systematic literature review. Issue 2 (18th February 2022) - Belyaeva, Elizaveta; Rubenstein, Ayelet; Pierson, Sheila K.; Dalldorf, Delaney; Frank, Dale; Lim, Megan S.; Fajgenbaum, David C.
Abstract: Idiopathic multicentric Castleman disease (iMCD) is a polyclonal lymphoproliferative disorder characterized by constitutional symptoms, generalized lymphadenopathy, cytopenias, and multi‐organ dysfunction due to excessive cytokines, notably Interleukin‐6. Idiopathic multicentric Castleman disease is often sub‐classified into iMCD‐TAFRO, which is associated with thrombocytopenia (T), anasarca (A), fever/elevated C‐reactive protein (F), renal dysfunction (R), and organomegaly (O), and iMCD not otherwise specified (iMCD‐NOS), which is typically associated with thrombocytosis and hypergammaglobulinemia. The diagnosis of iMCD is challenging as consensus clinico‐pathological diagnostic criteria were only recently established and include several non‐specific lymph node histopathological features. Identification of further clinico‐pathological features commonly found in iMCD could contribute to more accurate and timely diagnoses. We set out to characterize bone marrow (BM) histopathological features in iMCD, assess differences between iMCD‐TAFRO and iMCD‐NOS, and determine if these findings are specific to iMCD. Examination of BM specimens from 24 iMCD patients revealed a high proportion with hypercellularity, megakaryocytic atypia, reticulin fibrosis, and plasmacytosis across patients with both iMCD‐NOS and iMCD‐TAFRO with significantly more megakaryocytic hyperplasia ( p  = 0.001) in the iMCD‐TAFRO cases. These findings were also consistent with BM findings from 185 published cases of iMCD‐NOS and iMCD‐TAFRO. However, these findings are relatively nonspecific as they can be seen in various other infectious, malignant, and autoimmune diseases.